Trauma-Informed Care on mental health wards: staff and service user perspectives - Nikopaschos, Faye; Gibbons, Orla; Bailey, Emma; Foxall, Anna; Giachero, Camilla; Burrell, Gail (Frontiers in Psychology, 2025)
AimThis is the second study from a two-part evaluation into the impact of introducing Trauma-Informed Care (TIC) to a National Health Service (NHS) adult acute inpatient setting. The project consisted of two linked practices: Power Threat Meaning Framework (PTMF) Team Formulation, and a trauma-informed training program for staff, combined with the provision of Psychological Stabilisation resources. The first paper reported significant reductions in self-harm incidents and the use of restrictive practice on the wards. This paper aimed to elucidate experiences and mechanisms of change through a qualitative exploration of the impact of these new practices on staff and service users.MethodStaff (N = 7) and service users (N = 8) took part in semi-structured interviews about their experiences of the TIC project, which were subjected to Thematic Analysis.ResultsThematic analysis of staff interviews (N = 7) identified three main themes: ‘Changes in Knowledge and Understanding’, ‘Changes in Engagement and Practice’ and ‘Barriers and Constraints’. Thematic analysis of the service user interviews identified two main themes: ‘The Benefits of Stabilisation Interventions’ and ‘Trauma-Informed Care Helped my Recovery.’ConclusionStaff felt that the trauma-informed practices provided a meaningful conceptual framework for the better understanding of service users’ difficulties, which led to increased compassion and a wider range of helpful responses toward service user distress. Service users reported that they had gained new insights and skills, and been helped by their admission. The findings are considered in relation to the wider literature on TIC, and the benefits and challenges of introducing culture change in inpatient settings.